2006
DOI: 10.1056/nejmoa055191
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Gatifloxacin Therapy and Dysglycemia in Older Adults

Abstract: As compared with the use of other broad-spectrum oral antibiotics, including other fluoroquinolones, the use of gatifloxacin among outpatients is associated with an increased risk of in-hospital treatment for both hypoglycemia and hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
220
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(226 citation statements)
references
References 40 publications
3
220
2
1
Order By: Relevance
“…Both, hypoglycemic and hyperglycemic episodes occur during therapy [1,2]. Hypoglycemias are rare, however, they are potentially life-threatening and have led to a number of fatalities [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both, hypoglycemic and hyperglycemic episodes occur during therapy [1,2]. Hypoglycemias are rare, however, they are potentially life-threatening and have led to a number of fatalities [2].…”
Section: Introductionmentioning
confidence: 99%
“…While case reports of hypoglycemias exist for a number of fluoroquinolones, pharmacoepidemiologic evidence clearly documents an outstanding role of gatifloxacin as an inducer of hypoglycemias [1,2]. Since in one large trial the risk of other fluoroquinolones was found not to be different from that of other antibacterial drugs it has been supposed that the induction of glucose abnormalities is not a class effect of fluoroquinolones [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic and mortality data were obtained from the Ontario Health Insurance Plan Registered Persons Database, a registry of all Ontario residents with publically‐funded health insurance, and physicians’ services were identified using OHIP physician claims data. These databases were linked in an anonymous fashion using encrypted Ontario health card numbers, and are routinely used to study drug safety 27, 28, 29, 30, 31, 32.…”
Section: Methodsmentioning
confidence: 99%
“…Among the fluoroquinolones, the antimycobacterial activity is highest for moxifloxacin followed by levofloxacin and then ofloxacin, as evidenced by animal studies [22]. Use of gatifloxacin is not advised because of the many serious side effects such as dysglycemia [23]. Ciprofloxacin has hardly any anti-TB activity and should not be considered here [14,24].…”
Section: What Regimen To Start?mentioning
confidence: 99%